Rancang Bangun Sistem Pembelajaran SMP Nurul Islam Tanahbaya dengan Metode Agile Scrum - Nasywatus Sholichah, Nisa; Parga Zen, Bita; Ahmad Firdaus, Eryan; Mulyana, Dadan (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2025)
This study aims to design and develop a learning management system (LMS) at SMP Nurul Islam Tanahbaya using the Agile Scrum methodology. The developed system aims to enhance the effectiveness of the learning process by facilitating digital interaction between students and teachers and by providing an integrated platform for learning management. This study involves several stages, starting with problem identification, data collection, verification of needs and issues, Scrum process and development, testing, and conclusion drawing. The results of the study indicate that the application of the Agile Scrum method in the development of the LMS at SMP Nurul Islam Tanahbaya can improve development completion time and produce a system that meets the needs. This LMS features functionalities such as chats, material management, assignments, announcements, discussion forums, assessments, surveys, and recommendations. The Learning Management System (LMS) developed for SMP Nurul Islam Tanahbaya has been tested using blackbox testing methods. The results of the blackbox testing show that the system is valid and capable of performing all expected tasks effectively. Therefore, the developed LMS is expected to significantly contribute to improving the quality of learning at SMP Nurul Islam Tanahbaya and support a more effective and efficient educational process.